Nghiên cứu các yếu tố ảnh hưởng đến việc hòa tách bùn thải có chứa đồng của quá trình sản xuất bản mạch điện tử - Thu Huyền, Nguyễn Thị; Dũng, Đặng Trung; Tùng, Mai Thanh; Bích Thủy, Hoàng Thị (Vietnam Journal of Chemistry, 2017)
Copper recovery from waste mud of printed circuit boards (PCBs) via a three steps (leaching, filtration and electrowinning) process was studied. The copper mud was leached by the sulphuric acid leachant to form a concentrated copper ion solution for electrolysis. X-Ray diffraction, EDX, UV-Vis spectrophotometer, and ICP-MS analyses were done to characterize the structure and the ingredient of the solid samples and also determine the concentration of the liquid samples. The influences of the leaching solution content, concentration, time, temperature, ratio of solid and liquid phase, stirring speed and size of waste mud on the efficiency of waste mud leaching by sulfuric acid media were studied. The copper leaching was optimized done in the 1 M sulphuric acid solutions at room temperature for one hour. The solid/liquid phase ratio is 14 %, the copper mud grain size is 0.1 mm and the stirring speed is 600 rpm. The obtained results from this study are planning in the actual deployment of the Hanoi Urban Environment One Member Limited Company in Viet Nam. Keywords. Copper muds, leaching, PCBs fabrication.